Trends in abdominal aortic aneurysm-related mortality in Brazil, 2000–2016: a multiple-cause-of-death study (Clinics, 2021)
OBJECTIVES: Remarkable changes in the epidemiology of abdominal aortic aneurysm (AAA) have occurred in many countries during last few decades, which have also affected Brazilian mortality concurrently. This study aimed to investigate mortality trends related to AAA mortality in Brazil from 2000 to 2016. METHODS: Annual AAA mortality data was extracted from the public databases of the Mortality Information System, and processed by the Multiple Cause Tabulator. RESULTS: In Brazil, 2000 through 2016, AAA occurred in 69,513 overall deaths; in 79.6% as underlying and in 20.4% as an associated cause of death, corresponding to rates respectively of 2.45, 1.95 and 0.50 deaths per 100,000 population; 65.4% male and 34.6% female; 60.6% in the Southeast region. The mean ages at death were 71.141 years overall, and 70.385 years and 72.573 years for men and women, respectively. Ruptured AAA occurred in 64.3% of the deaths where AAA was an underlying cause, and in 18.0% of the deaths where AAA was an associated cause. The standardized rates increased during 2000–2008, followed by a decrease during 2008–2016, resulting in an average annual percent change decline of -0.2 (confidence interval [CI], -0.5 to 0.2) for the entire 2000–2016 period. As associated causes, shock (39.2%), hemorrhages (33.0%), and hypertensive diseases (26.7%) prevailed with ruptured aneurysms, while hypertensive diseases (29.4%) were associated with unruptured aneurysms. A significant seasonal variation, highest during autumn and followed by in winter, was observed in the overall ruptured and unruptured AAA deaths. CONCLUSIONS: This study highlights the need to accurately document epidemiologic trends related to AAA in Brazil. We demonstrate the burden of AAA on mortality in older individuals, and our results may assist with effective planning of mortality prevention and control in patients with AAA.